2002
DOI: 10.1159/000064245
|View full text |Cite
|
Sign up to set email alerts
|

Sorption Isotherms of Acetone on Various Building Materials

Abstract: The physical modelling of Indoor Air Quality (IAQ) suffers a lack of sorption data for the most common Volatile Organic Compounds (VOC) on building materials. This paper deals with an experimental facility that aimed to provide the sorption isotherms of gaseous contaminants on various materials. It was used to determine the sorption isotherms of acetone on chipboard, acrylic paint, and the gypsum core of commercially available gypsum board. After a brief introduction to fundamental principles of sorption, the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
16
0

Year Published

2003
2003
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 15 publications
3
16
0
Order By: Relevance
“…As far as the measurement of D m and K is concerned, many kinds of methods have been proposed by virtue of sorption or emission test in environmental chambers, which can measure the D m and K respectively or simultaneously. Tiffonnet et al put forward a multi-sorption method to determine K [18]. Cox et al proposed a microbalance method to obtain K and D m [19].…”
Section: Introductionmentioning
confidence: 99%
“…As far as the measurement of D m and K is concerned, many kinds of methods have been proposed by virtue of sorption or emission test in environmental chambers, which can measure the D m and K respectively or simultaneously. Tiffonnet et al put forward a multi-sorption method to determine K [18]. Cox et al proposed a microbalance method to obtain K and D m [19].…”
Section: Introductionmentioning
confidence: 99%
“…As shown in Table 3.2, it results in a 41, 53 and 28 per cent decrease in the absorption coefficient when the temperature is increased from 25°C to 35°C. Tiffonnet et al (2002) found a lower heat of absorption of -7.5 kJ/mol for acetone in acrylic paint, reflecting slighter changes in K H with temperature (see Table 3.2). Finally, still based on the results of Tiffonnet et al (2002), the acetone heat of adsorption in particle board would have a value of about -30 kJ/mol -that is to say, the same order of magnitude as typical heats of absorption in polymers.…”
Section: Influence Of Temperature On Diffusivitiesmentioning
confidence: 94%
“…Tiffonnet et al (2002) found a lower heat of absorption of -7.5 kJ/mol for acetone in acrylic paint, reflecting slighter changes in K H with temperature (see Table 3.2). Finally, still based on the results of Tiffonnet et al (2002), the acetone heat of adsorption in particle board would have a value of about -30 kJ/mol -that is to say, the same order of magnitude as typical heats of absorption in polymers. However, there is too little data to draw definitive conclusions on the compared temperature sensitivity of K p and K H .…”
Section: Influence Of Temperature On Diffusivitiesmentioning
confidence: 94%
See 1 more Smart Citation
“…Recently particularly in Japan, there has been a lot of interest in the use of sorptive building materials to reduce the concentrations of VOCs and formaldehyde in indoor environments [57][58][59][60][61][62][63][64][65][66]. The mass transfer coefficients, material loading and air change rate can influence the sorptive behaviour, particularly in respect to formaldehyde concentration in air [58,67].…”
Section: Indoor Sinks Sorption and Diffusion Layermentioning
confidence: 99%